Balancing in the margins of gender: exploring psychologists' meaning-making in their work with gender non-conforming youth seeking puberty suppression. Issue 2 (3rd April 2019) - Jessen, Reidar Schei; Roen, Katrina
ABSTRACT: The past 15 years have seen the growth of puberty suppression as the prevailing approach to supporting gender non-conforming children and youth. Puberty suppression is considered to provide time for weighing up the pros and cons of medical transition. Research based on binary understandings of gender has demonstrated that a carefully selected group of gender non-conforming youth benefit from physical treatment and gender transition, but the research that details how psychologists can best support young people during this time is limited. This is the gap addressed by the current research. The purpose of the present study is to explore the meaning-making framework within which some clinical psychologists and gender non-conforming youth approach discussions of puberty suppression. Five semi-structured interviews were conducted with clinical psychologists working with gender non-conforming youth. The data were analysed using thematic analysis. The results indicate that there is pressure on gender non-conforming youth, often coming from families, friends and mass media, to buy into heteronormative and binary discourses regarding gender and what constitutes a good life. The results also indicate that the participants deploy affirmative and exploratory therapeutic strategies in their work, in order to enable gender non-conforming youth to make informed decisions regarding puberty suppression. Participants emphasized the importance of therapeutic approaches that explore non-binary gender discourses, alongside the use of puberty suppression and other medical interventions that enable clients to fit more with gender norms. The therapeutic balance between affirmation and exploration may shed light on how both research within the binary tradition and critics of binary assumptions are in danger of oversimplifying the process of gender identity development. This research highlights the importance of understanding the complex negotiation of gender discourses that are in tension with one another.